In-House Training: Penerapan Teknologi AI Generatif dalam Pendidikan di SDN 1 Kenongo - Silviana, Lailatul Ilmi (Maliki Interdisciplinary Journal, 2025)
A data from a survey distributed by the Student Work Lecture group (KKM) 22 UIN Malang in 2025 shows that 5 out of 6 teachers at SDN 1 Kenongo are not capable of using AI. The teachers’ ignorance and unfamiliarity with AI technology at least gives them a sense of lack of confidence in the process of teaching and learning activities. After an initial survey, the KKM 22 group saw this as a problem that needed to be addressed. As an answer, an In-House Training Artificial Intelligence became one of the work programs of the Education division of group 22. By not only focusing on the introduction of AI, this activity also directly contains a practice session for writing prompts. Several functions such as creating questions and creating lesson plans have been well learned by the teachers of SDN 1 Kenongo in this practical session. In the end, this 150-minute activity succeeded in providing a good understanding of AI and bringing the readiness of teachers at SDN 1 Kenongo to start applying AI in teaching and learning activities.